2008
DOI: 10.1016/j.jfa.2007.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Metaplectic representation on Wiener amalgam spaces and applications to the Schrödinger equation

Abstract: We study the action of metaplectic operators on Wiener amalgam spaces, giving upper bounds for their norms. As an application, we obtain new fixed-time estimates in these spaces for Schrödinger equations with general quadratic Hamiltonians and Strichartz estimates for the Schrödinger equation with potentials V (x) = ±|x| 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
96
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 35 publications
(104 reference statements)
3
96
0
Order By: Relevance
“…There it was shown that A is bounded as an operator (F L p ) comp → (F L p ) loc , 1 ≤ p ≤ ∞, if m ≤ −d 1 2 − 1 p . This is similar to (5), but with the difference of one unit in the dimension. Surprisingly, this threshold was shown to be sharp in any dimension d ≥ 1, even for phases linear with respect to η; see [7] (or Sect.…”
Section: Introductionmentioning
confidence: 81%
“…There it was shown that A is bounded as an operator (F L p ) comp → (F L p ) loc , 1 ≤ p ≤ ∞, if m ≤ −d 1 2 − 1 p . This is similar to (5), but with the difference of one unit in the dimension. Surprisingly, this threshold was shown to be sharp in any dimension d ≥ 1, even for phases linear with respect to η; see [7] (or Sect.…”
Section: Introductionmentioning
confidence: 81%
“…In fact, there are some recent works which have been devoted to the study of the well-posedness for a class of nonlinear evolution equation in modulation spaces; cf. [2,3,5,7,8,9,20,24,25,26,31,39,40,41,42]. Our main goal of this paper is to study the global well-posedness of 4NLS in modulation spaces M 3+1/2 2,1…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in [23], the main point was a decomposition of T into a part with phase which is nondegenerate with respect to η (and further factorized) and a degenerate part, with a phase closer to the linear case, fulfilling better estimates. However, as example (5) shows, the case of linear phases in η already contains all the obstructions to the local FL p -boundedness, so that we cannot here take advantage of this kind of decomposition. Instead, the proof of Theorem 1.1 makes use of the theory of modulation spaces M p , 1 ≤ p ≤ ∞, which are now classical function spaces used in time-frequency analysis (see [8,9,12] and Section 2 for the definition and properties).…”
Section: Introductionmentioning
confidence: 99%